Enhancing Project Management for SMEs: A Hybrid Approach - Ayanda Sibiya; Bongani Sibiya; Johan Jordaan; Brian Ngwako Mahosi (Journal of Management and Entrepreneurship Research, 2023)
Objective: South Africa's economic growth and development are closely intertwined with government-prioritized infrastructure development projects. However, SMEs in this sector often grapple with insufficient project management processes, impeding their efficacy and economic contributions. The issue stems from the inadequate implementation of project management methodologies by SMEs, which adversely affects project outcomes and consequently their economic impact. Research Design & Methods: A literature review was conducted to assess the implementation of project management methodologies by SMEs in South African infrastructure development projects. The objective is to highlight areas for improvement, rectify the deficiency in project management practices among SMEs, and bolster their effectiveness and economic contributions. Findings: Preliminary findings accentuate the critical role of project management as a discipline for SMEs involved in infrastructure projects. Its absence or inadequate implementation hampers the growth and sustainability of organizations aiming to make substantial economic contributions and create employment. A hybrid project management model tailored for SMEs in infrastructure development emerges as a mechanism for effectively managing infrastructure projects. Implications and Recommendations: The conceptualization of a hybrid project management model for infrastructure development projects holds the potential to enhance project value by facilitating adaptability. By incorporating agile project management components, this model also stands to improve client engagement, consequently elevating the prospects of success in infrastructure development projects. Contribution & Value Added: This study contributes to the understanding of how SMEs can improve their effectiveness and economic contributions in South Africa's infrastructure development sector. The proposed hybrid project management model offers valuable insights for practitioners and policymakers in South Africa, ultimately fostering economic development and sustainable growth in the country.